Analysis of Questions in Grade VIII Mathematics Textbooks Revised Edition 2017 Published by the Ministry of Education and Culture Based on the Cognitive Dimensions of TIMSS 2019 - Yuliany, Nur; Halimah, Andi; Sabria,; Munawarah,; Thalhah, Sitti Zuhaerah (Alauddin Journal of Mathematics Education, 2023)
This study aims to describe the first semester and second semester competency test questions contained in the revised 2017 edition of the junior high school mathematics textbook based on the cognitive dimensions of TIMSS 2019. This type of research is descriptive research using a qualitative approach. The data source in this study is the first semester competency test questions and the second semester competency test contained in the 2017 revised edition of the SMP/MTs grade VIII mathematics textbook written by Abdur Rahman As'ari, Mohammad Tohir, Erik Valentino, Zainul Imron and Ibnu Taufiq entitled "Mathematics" SMP/MTs grade VIII. The data collection technique used in this study is to use the documentation method. The results of data analysis show that questions with the cognitive dimension of knowledge (knowing) dominate the number material which is characterized by the explicit presentation of the problem so that in the process of solving the problem without doing the analysis first. Then the problem with the cognitive dimension of applying dominates the geometry material which is characterized by the presentation of problems in the form of routine problems with the cognitive process of solving problems using concepts and presenting mathematical information into mathematical models, and problems with the cognitive dimension of reasoning dominate algebraic material which is the highest cognitive level and the presentation of the problem is in the form of non-routine problems.